Social Interdependence and Micro-Foundations: A Literature Review - Katarzyna PIÓRKOWSKA (Communications of International Proceedings, 2024)
The paper fills the research gap concerning a theoretical background for the micro-foundational perspective of social interdependence. It aims to explore the concept of social interdependence from the micro-foundations perspective. The method that has been used is a systematic and critical literature review of the following concepts: micro-foundations, Coleman’s diagram, emergence and interaction, interdependence, social interdependence, multi-level approach, and methodological individualism. The overarching findings involves the following research propositions. (P1) Individual dispositions determines individual actions. (P2) Individual actions determine individual outcomes, team outcomes, and organisational outcomes. (P3) The links between individual actions and individual outcomes, team outcomes, and organisational outcomes is mediated with interaction patterns and psychological processes effects. (P4) Individual outcomes, team outcomes, and organisational outcomes are determined by organisational conditions. (P5) Organisational conditions enhance or hinder individual dispositions.
Keywords: multi-level research; micro-foundations; interdependence; social interdependence.